Impact of COVID-19 research: a study on predicting influential scholarly documents using machine learning and a domain-independent knowledge graph - Rabby, Gollam; D'Souza, Jennifer; Oelen, Allard; Dvorackova, Lucie; Svátek, Vojtěch; Auer, Sören (Journal of biomedical semantics, 2023)
Multiple studies have investigated bibliometric features and uncategorized scholarly documents for the influential scholarly document prediction task. In this paper, we describe our work that attempts to go beyond bibliometric metadata to predict influential scholarly documents. Furthermore, this work also examines the influential scholarly document prediction task over categorized scholarly documents. We also introduce a new approach to enhance the document representation method with a domain-independent knowledge graph to find the influential scholarly document using categorized scholarly content. As the input collection, we use the WHO corpus with scholarly documents on the theme of COVID-19. This study examines different document representation methods for machine learning, including TF-IDF, BOW, and embedding-based language models (BERT). The TF-IDF document representation method works better than others. From various machine learning methods tested, logistic regression outperformed the other for scholarly document category classification, and the random forest algorithm obtained the best results for influential scholarly document prediction, with the help of a domain-independent knowledge graph, specifically DBpedia, to enhance the document representation method for predicting influential scholarly documents with categorical scholarly content. In this case, our study combines state-of-the-art machine learning methods with the BOW document representation method. We also enhance the BOW document representation with the direct type (RDF type) and unqualified relation from DBpedia. From this experiment, we did not find any impact of the enhanced document representation for the scholarly document category classification. We found an effect in the influential scholarly document prediction with categorical data.
Keywords: jazyk (prostředek komunikace); Influential scholarly document prediction; Text mining; algoritmy; COVID-19; Pattern Recognition, Automated; Humans; rozpoznávání automatizované; Machine Learning; Machine learning algorithms; Algorithms; Domain-independent knowledge graph; World health organization; lidé; strojové učení; Language